The Impact of Covid 19 and Commodification on Tourism Religious Islam: From Spiritual for Experience Tour - Lestari, Mei (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Governments around the world are deeply concerned about how difficult it is for Hajj pilgrims to halt their travel movements during COVID-19 restrictions and national lockdown periods. This pandemic has had a significant impact on pilgrimage tourism in Mecca because since 2020, gatherings at pilgrimage sites have been prohibited. In other words, the Saudi government expanded the hospitality, tourism, and telecommunications sectors in general and modernized Mecca's tourism infrastructure in particular, turning it into a modern city, to take advantage of the increasing demand for religious tourism and to maximize economic benefits (Pecenoni et al., 2012). The desire for increased luxury and comfort suggests that the Hajj has evolved into a more